CFD simulation of membrane-based energy recovery ventilator in air-conditioning system with experimental validation - Subas Chandra Bose Magesh (2018)
Energy savings is one of the most popular topics among the researchers across the world. Furthermore, the energy saving of Heating, Ventilating and Air Conditioning (HVAC) system in buildings is a most considerable factor since 40 to 50% of energy is consumed for air conditioning. To make an efficient way for energy saving, the energy recovery ventilator (ERV), or the heat recovery ventilator (HRV), is integrated with the HVAC system to reduce the energy consumption. In general, the ERV works as an analogy of a cross-counterflow heat exchanger plate. The two channels of the ERV are separated by the hydrophilic membrane. The guiding walls which are on either side of the hydrophilic membrane guide the airflow flowing through the channels. By preconditioning the air entering the air-conditioning unit, it is possible to reduce the energy consumption of the air conditioning unit. The ERV is involved in transferring the heat and moisture between the outdoor air entering the air-conditioning unit and the indoor air leaving the air-conditioning unit. This drastically reduces the power consumption of the air-conditioning unit. Therefore, the main objective of this study is to analyze the ERV performance employing Computational Fluid Dynamics (CFD) simulation with the validation of the experimental works. The performance of the ERV membrane is carried out by COMSOL multi-physics. The analysis is performed for various parameters, such as the flow rate, the humidity ratio, the temperature of the outdoor air condition as in countries of the tropical climate, such as in Singapore. The efficiency of the ERV membrane is evaluated. The heat transferred and the mass diffused through the membrane are obtained. Apart from that, the experiment is also conducted for investigating the ERV performance. The experiments are investigated for the outdoor air conditions of temperature and relative humidity ranging from 28 to 35°C and 50 to 80%. ERV in the experimental setup consists of the 100 units connecting to the inlets and outlets. The experimental data are recorded using an NI LabVIEW software with the sensors and Data Acquisition (DAQ) hardware arrangement. The test bed is constructed in such way to replicate the outdoor air condition by incorporating the heater and humidifier arrangement, such that air stream in Inlet I could be manipulated for various outdoor air conditions. From the experimental results, it is shown that the efficiency of the ERV reaches the maximum at a flow rate ranging from 1.5 to 2.5 m/s, the temperature from 33.5 to 35°C, and the relative humidity from 60 to 70%. The maximum recovered total energy is 1.25 kW at the outdoor air temperature, relative humidity of 35°C and 65% respectively. From both the simulation and the experiment results, it is demonstrated that the implementation of ERV in HVAC system paves the way to save energy of the buildings under the optimum outdoor air condition. The ERV can work with the sensible and latent efficiency of 80% and 70% respectively. Several key parameters, including the temperature, humidity ratio and airflow velocity, influence the ERV performance significantly. In the future, the study of the hydrophilic membrane in the ERV will be recommended to improve the sensible efficiency and latent efficiency.